Intelligent complex adaptive systems - Yang, Ang; Shan, Yin (IGI Pub., 2008)
"This book explores the foundation, history, and theory of intelligent adaptive systems, providing a fundamental resource on topics such as the emergence of intelligent adaptive systems in social sciences, biologically inspired artificial social systems, sensory information processing, as well as the conceptual and methodological issues and approaches to intelligent adaptive systems"--Provided by publisher.